The role of B-1 cells in cancer progression and anti-tumor immunity - Rodríguez-Zhurbenko, Nely; Hernández, Ana M. (Frontiers in Immunology, 2024)
Abstract In recent years, in addition to the well-established role of T cells in controlling or promoting tumor growth, a new wave of research has demonstrated the active involvement of B cells in tumor immunity. B-cell subsets with distinct phenotypes and functions play various roles in tumor progression. Plasma cells and activated B cells have been linked to improved clinical outcomes in several types of cancer, whereas regulatory B cells have been associated with disease progression. However, we are only beginning to understand the role of a particular innate subset of B cells, referred to as B-1 cells, in cancer. Here, we summarize the characteristics of B-1 cells and review their ability to infiltrate tumors. We also describe the potential mechanisms through which B-1 cells suppress anti-tumor immune responses and promote tumor progression. Additionally, we highlight recent studies on the protective anti-tumor function of B-1 cells in both mouse models and humans. Understanding the functions of B-1 cells in tumor immunity could pave the way for designing more effective cancer immunotherapies.